The interplay of body mass index, gestational weight gain, and birthweight over 3800 g in vaginal breech birth: A retrospective study - Henriette Tautenhahn; Anne Dathan‐Stumpf; Noura Kabbani; Holger Stepan; Massimiliano Lia (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Optimal counseling of women for vaginal breech birth requires consideration of both established and emerging risk factors for adverse perinatal outcomes. Currently, rising prevalences of maternal obesity and impaired glucose tolerance challenge obstetric care. We aimed to investigate the effects of these parameters on the outcome of vaginal breech birth to improve counseling practices. Material and Methods A total of 361 women (without previous vaginal births) attending vaginal birth of a singleton fetus in breech presesntation between 01/2015 and 11/2021 were included in this retrospective single‐center study. Data were derived from the hospital data base. We analyzed the effect of the maternal body mass index (BMI) at birth (compared to pre‐pregnancy BMI), excessive weight gain, gestational diabetes, and neonatal birthweight on obstetrical and neonatal short‐term outcomes (intrapartum cesarean delivery, performance of obstetric maneuvers (Løvset‐, Bracht‐, Veit‐Smellie maneuver and Bickenbach's arm delivery), admission to the neonatal unit, Apgar score after 5 minutes <7, and arterial cord pH‐value <7.10). Multivariable logistic regression was used for analysis and adjustment of variables. Results Overall, 246 women (68.1%) had a successful vaginal birth. Intrapartum cesarean delivery (n = 115/361; 31.9%) was independently associated with maternal BMI at birth (p = 0.0283, aOR = 1.87 (1.19–3.97)) if birthweight was ≥3800 g. The rate of intrapartum cesarean delivery was also higher in women with gestational diabetes (p = 0.0030, aOR = 10.83 (2.41‐60.84)). A significantly higher risk of neonatal acidosis (arterial pH‐value <7.10) was observed in women with BMI at birth ≥30 kg/m2 (p = 0.0345, aOR = 1.84 (1.04–3.22)) without affecting other outcomes. Pre‐pregnancy BMI, gestational weight gain and BMI‐gain did not significantly affect the obstetrical and neonatal birth outcomes. Conclusions When neonatal birthweight is ≥3800 g, maternal BMI at birth (p = 0.0283; aOR = 1.87 (1.19–3.97)) is independently associated with the rate of intrapartum cesarean delivery. However, pre‐pregnancy BMI and BMI‐gain during pregnancy were not associated with the need for intrapartum cesarean delivery or other adverse outcomes. Consequently, BMI at the time of birth could be more informative than pre‐pregnancy BMI and may improve counseling of women attempting vaginal breech birth.